Anaphora and Subjectification in Lexicalized Feminine Clitic Constructions - José Luis Cifuentes Honrubia (Universitat Autònoma de Barcelona, 2020)
In this paper I will examine anaphoric relationships in lexicalized feminine clitic constructions (dormirla [to sleep it off], pirárselas [to beat it], etc.). Lexicalized feminine clitic constructions have no syntactic reference for the clitic, but there is an implicit contextual semantic reference to an implicated and recognized concept. Given the diversity of lexicalized feminine clitic constructions, an attempt is going to be made to establish a growing speaker subjectification continuum depending on whether it is a contextual semantic reference from an accommodation in a singular context, in a multiple context, or we are faced with a conventional implication. We will also comment on other more complicated processes, either because the construction experiences changes in its meaning or because the analogy causes the presence of the feminine clitic.